Evaluasi Keterlambatan Pembangunan Jalan Perkerasan Lentur (Flexible Pavement) Studi Kasus : Proyek Pembangunan Jalan Rajawali Sakti Dan Jalan Bima Kecamatan Tampan Pekanbaru) - Muhammad Zikri; Hendra Taufik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Construction project on Rajawali and Bima street in Tampan district had delayed up to 33 days from the time of execution of project should have been completed in 110 days. The evaluation done on critical path of project had reveal that poor project management is the main cause of delay. Project delay can be overcome by rescheduling and accelerating work settlement on critical path. Some alternative method that such as addition of workers, equipment and also shift system can be done to accelerate the period of particular work settlement. The difference of each method revealed by the comparison of overtime work productivity calculation method, addition of workers and equipment productivity calculation method, also shift system productivity calculation method. The result of analysis had shown the cost of overtime work alternative method was Rp 134.465.669,63 addition of workers and equipment alternative method was Rp 237.375.404,80 and system shift alternative method was Rp 146.636.930,40. Also additional cost for overwork productivity method was Rp 79.285.459,23 addition of workers and equipment was Rp 185.815.046,26 and shift system productivity method was Rp 192.746.756,20.Keywords:alternative method, productivity calculation method, overwork, addition of workers and equipment, shift system.